2020
DOI: 10.1155/2020/1078365
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the ROS-EGFR Pathway Mediates the Protective Action of Nox1/4 Inhibitor GKT137831 against Hypertensive Cardiac Hypertrophy via Suppressing Cardiac Inflammation and Activation of Akt and ERK1/2

Abstract: Oxidative stress, inflammation, and hypertension constitute a self-perpetuating vicious circle to exacerbate hypertension and subsequent hypertensive cardiac hypertrophy. NADPH oxidase (Nox) 1/4 inhibitor GKT137831 alleviates hypertensive cardiac hypertrophy in models of secondary hypertension; however, it remains unclear about its effect on hypertensive cardiac hypertrophy in models of essential hypertension. This study is aimed at determining the beneficial role of GKT137831 in hypertensive cardiac hypertrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Previous studies had indicated that inhibition of EGFR activity protected against progressive DN in T1 DM and T2 DM [ 48 ]. Zeng et al concluded that EGFR inhibition reduced ROS production in the left ventricle and blunted hypertensive myocardial hypertrophy in spontaneously hypertensive rats [ 49 ]. Therefore, the EGFR tyrosine kinase inhibitor resistance may have a common effect to accelerate the progression of DM with HF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies had indicated that inhibition of EGFR activity protected against progressive DN in T1 DM and T2 DM [ 48 ]. Zeng et al concluded that EGFR inhibition reduced ROS production in the left ventricle and blunted hypertensive myocardial hypertrophy in spontaneously hypertensive rats [ 49 ]. Therefore, the EGFR tyrosine kinase inhibitor resistance may have a common effect to accelerate the progression of DM with HF.…”
Section: Discussionmentioning
confidence: 99%
“…Edges represent proteinprotein associations, and the line thickness indicates the strength of data support. inhibition reduced ROS production in the left ventricle and blunted hypertensive myocardial hypertrophy in spontaneously hypertensive rats [49]. Therefore, the EGFR tyrosine kinase inhibitor resistance may have a common effect to accelerate the progression of DM with HF.…”
Section: Enrichment Analysis Based On Core Targetsmentioning
confidence: 97%
“…Various evidences have supported the roles of EGFR in ROS-induced cellular response 32 - 37 . EGFR level was considerably reduced when cells were exposed to IBRV infection and 4-min CAP treatment followed by 46 h culturing (p<0.001, Figure 2 A ).…”
Section: Resultsmentioning
confidence: 99%
“…It is also well tolerated and delays or prevents the progression of a range of cardiovascular disorders. For example, GKT137831 attenuated plaque formation by inhibiting ROS generation and reducing the adhesion of inflammatory cells to the vascular wall ( Gray et al, 2013 ); it also markedly attenuated cardiac remodeling by decreasing ROS levels ( Zhao et al, 2015 ) and attenuated hypertensive cardiac hypertrophy by suppressing cardiac inflammation and activating Akt and ERK1/2 ( Zeng SY. et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%